FRAKSI ETANOL RIMPANG TEMU PUTIH (Curcuma zedoaria (Christm.) Rosc.) SEBAGAI ANTIFUNGI TERHADAP Candida albicans dan Trichophyton rubrum - Yuli Wahyu Trimulyani; Nurma Suri; Niken Dwi Astarina (JFL : Jurnal Farmasi Lampung, 2018)
Traditional medicine is used as natural because it has small effects and more economical than the synthetic drugs. One example of the plants used as a Traditional medicine are Curcuma zedoaria. The study to examine the activity fraction of Curcuma zedoaria rhizome ethanol extract agains Candida albicans and Trichophyton rubrum. The simplisia of Curcuma zedoaria rhizome was extracted with ethanol 70% using a maceration method. Thick extracts were then fractionated using saveral solven such as n-heksane, chloroform and ethanol. The testing method used disc antifungi activity with the concentration of 6.25%, 12.5%, 25%, 50%, 75%, ketokonazol as the positive control and aquades as the resolvent. The test compounds Thin Layer Chromatography (TLC) method with eluen chloroform: methanol: water (2:3:5(v/v/v)) and phase uses G60F254 had been done. The result showed that Curcuma zedoaria rhizome significantly inhibit of C. albicans and T. rubrum the best inhibit zone diameter that are concentration of 75% for both of them with a diameter 8.98 mm in C. albicans and 11.66 mm in T. rubrum. Minimum Inhibitory Concentration (MIC) C. albicans is obtained on concentration of 6.25% and T. rubrum is concentration on of 12.5%. The TLC results showed a compound of flavonoids (Rf 0.88), saponins (Rf 0.74), tannins (Rf 0.86). Minimum Inhibitory Concentration (MIC) in C. albicans and T. rubrum are fungistatik and Minimum Bactericidal Concentration (MBC) are not fungisid for both of them. The ethanol fraction of Curcuma zedoaria rhizome has an activity as an antifungal against C. albicans and T. Rubrum with flavonoids, tannins and saponins. Keywords: Antifungi, Candida albicans, Curcuma zedoaria, Fungistatic, Trichophyton rubrum.